Vulvar Malignancy in Neurofibromatosis Syndrome - Angela Musella; Innocenza Palaia; Lavinia Domenici; Assunta Casorelli; Angela Martoccia; Pierluigi Benedetti Panici (Case Reports in Obstetrics and Gynecology)
Type 1 neurofibromatosis (NF1) is a dominantly inherited neurologic disorder that affects primarily the skin, bones, and peripheral nervous system. It may be associated with a variety of clinical manifestations including cafe-au-lait spots, skinfold freckling, Lisch nodules, and visceral neurofibromas. Individuals affected by NF1 harbor an increased risk for both benign and malignant tumors. Malignant transformation is usually observed in the form of neurosarcoma. Rarely, NF1 affects the genital tract, and isolated vulvar localization is extremely rare. Here is reported a rare case of a solitary neurosarcoma of the vulva in a 43-year-old woman affected by NF1 syndrome treated with surgical excision. The purpose of this case is to underline the possibility of association between NF1 and genital tract sarcoma and to suggest an accurate evaluation of rapid growth vulvar mass in this setting.